MoWa: A Disinfectant for Hospital Surfaces Contaminated With Methicillin-Resistant Staphylococcus aureus (MRSA) and Other Nosocomial Pathogens - Gregory, Tyler V.; Ellis, Karen; Valeriani, Renzo; Khan, Faidad; Wu, Xueqing; Murin, Landon; Alibayov, Babek; Vidal, Ana G. Jop; Zhao, Tong; Vidal, Jorge E. (Frontiers in Cellular and Infection Microbiology, 2021)
Introduction Staphylococcus aureus strains, including methicillin-resistant S. aureus (MRSA) and methicillin-sensitive S. aureus (MSSA), are a main cause of nosocomial infection in the world. The majority of nosocomial S. aureus-infection are traced back to a source of contaminated surfaces including surgery tables. We assessed the efficacy of a mixture of levulinic acid (LA) and sodium dodecyl sulfate (SDS), hereafter called MoWa, to eradicate nosocomial pathogens from contaminated surfaces. Methods and Results A dose response study demonstrated that MoWa killed 24 h planktonic cultures of S. aureus strains starting at a concentration of (LA) 8.2/(SDS) 0.3 mM while 24 h preformed biofilms were eradicated with 32/1.3 mM. A time course study further showed that attached MRSA bacteria were eradicated within 4 h of incubation with 65/2 mM MoWa. Staphylococci were killed as confirmed by bacterial counts, and fluorescence micrographs that were stained with the live/dead bacterial assay. We then simulated contamination of hospital surfaces by inoculating bacteria on a surface prone to contamination. Once dried, contaminated surfaces were sprayed with MoWa or mock-treated, and treated contaminated surfaces were swabbed and bacteria counted. While bacteria in the mock-treated samples grew at a density of ~104 cfu/cm2, those treated for ~1 min with MoWa (1.0/0.04 M) had been eradicated below limit of detection. A similar eradication efficacy was obtained when surfaces were contaminated with other nosocomial pathogens, such as Klebsiella pneumoniae, Pseudomonas aeruginosa, Acinetobacter baumannii, or Staphylococcus epidermidis. Conclusions MoWa kills planktonic and biofilms made by MRSA and MSSA strains and showed great efficacy to disinfect MRSA-, and MSSA-contaminated, surfaces and surfaces contaminated with other important nosocomial pathogens.